The effect of pharmacist-led education on inhaler use skills in hospitalised patients with chronic obstructive pulmonary disease - OKUYAN, BETÜL; SANCAR, MESUT (BMJ PUBLISHING GROUP, 2015)
Objective To assess patient inhalation skills and the effect of pharmacist-led education on these skills in chronic obstructive pulmonary disease (COPD) patients using inhalers in a hospital setting. Methods Pre- and 1month post-intervention were evaluated by scoring essential steps during inhaler use for each inhaler device. Results 41 patients participated in the study (mean age 64.3611.78 years, range 29-83 years). The female-male ratio was 7:34. Patients' inhaler administration skills were found to be improved by pharmacist-led education (p<0.05). Conclusions Evaluation of accurate inhaler device usage in patients with COPD should be performed periodically, and training regarding the inhaler device should be reconsidered according to the needs of patients.
Keywords: RESPIRATORY MEDICINE (see Thoracic Medicine); CLINICAL PHARMACY; EDUCATION & TRAINING (see Medical Education & Training); ASTHMA; INHALATION; DEVICES; LIFE